2009
DOI: 10.3109/09513590903159615
|View full text |Cite
|
Sign up to set email alerts
|

Anti muellerian hormone serum levels in women with endometriosis: A case–control study

Abstract: Lower AMH serum levels and an association with the severity were found in women with endometriosis. Physicians have to be aware of this fact. Because of the expected lower response on a controlled ovarian hyperstimulation (COH), AMH serum level should be measured to optimise the dose of gonadotropin treatment previous to a COH, especially in women with severe endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(31 citation statements)
references
References 20 publications
1
27
1
2
Order By: Relevance
“…The mean serum AMH level of the 141 patients with endometrioma (group 2) was significantly lower compared to the 1,323 patients without endometrioma (control group) (Figures 1, 2, Table 2). Shebl et al reported that AMH levels were significantly lower in patients with severe endometriosis than in the control group [22]. In agreement with Shebl's reports, we also found that patients with ovarian endometriomas had significantly lower serum AMH levels compared with patients without endometriomas.…”
Section: Discussionsupporting
confidence: 92%
“…The mean serum AMH level of the 141 patients with endometrioma (group 2) was significantly lower compared to the 1,323 patients without endometrioma (control group) (Figures 1, 2, Table 2). Shebl et al reported that AMH levels were significantly lower in patients with severe endometriosis than in the control group [22]. In agreement with Shebl's reports, we also found that patients with ovarian endometriomas had significantly lower serum AMH levels compared with patients without endometriomas.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, contradictory results also exist 26,27. The majority of previous studies regarding AMH value in endometriosis patients have focused on infertile patients participating in IVF 8,28. However, to explain the risk of reduced fecundity in endometriosis patients, ovarian reserve should be evaluated among the general population, regardless of existence of infertility.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study noted that infertile patients with endometriosis exhibit decreased serum anti-mullerian hormone (AMH) levels compared to male factor infertility, and advocated that measuring AMH may be beneficial in optimizing the dose needed for gonadotropin treatment prior to ovarian stimulation 8. Moreover, further research suggested similarities in ovarian reserve in infertility patients with minimal/mild endometriosis compared to patients with tubal obstruction 9.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was demonstrated that infertile patients with minimal and mild endometriosis had lower serum MIS levels compared to a cohort of infertility patients with tubal occlusion but no endometriosis [29]. However, serum MIS levels do not show a significant fluctuation during a spontaneous menstrual cycle.…”
Section: Discussionmentioning
confidence: 99%